EVALUATION OF INDIGOTIN CONTENT IN INDIGO POWDER COLLECTED FROM TWO PLANT SPECIES DISTRIBUTED IN LAM DONG PROVINCE - Ngoc, Nguyen Van (TNU Journal of Science and Technology, 2024)
Indigofera cassioides Rottl. ex Bl. and Indigofera suffruticosa Mill., which are widely distributed in Lam Dong province, serve as a natural source of indigo color. Indigo powder, known for its inherent indigo color, has been used by humans for dyeing and medicinal purposes for a long time. However, no global research has investigated the extraction efficiency of indigo powder and the indigotin content from these two indigo species. This study aimed to evaluate the extraction efficiency of indigo powder and measure the indigotin content in both the powder and fresh leaves of these species in Lam Dong. The indigo powder was obtained using the maceration extraction method, and the indigotin content was determined through spectrophotometry using a JASCO V-730 spectrophotometer (UV- VIS). The results showed that the efficiency of extracting and collecting indigo powder from these two species was 4.61 ± 0.30% for I. cassioides and 4.23 ± 0.92% for I. suffruticosa. The indigotin content in I. cassioides indigo powder was found to be 2.83 ± 0.467%, while in I. suffruticosa indigo powder, it was 8.80 ± 2.12%. This corresponds to an indigotin content in fresh leaves of I. cassioides and I. suffruticosa samples of 0.13 ± 0.02% and 0.37 ± 0.09%, respectively.